Analisis Sentimen Aplikasi Novel Online Di Google Play Store Menggunakan Algoritma Support Vector Machine (SVM) - Nurhafida, Selva Indah; Sembiring, Falentino (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Following the COVID-19 outbreak, many people were forced to leave their employment due to layoffs in various companies, forcing them to seek other ways to pass the time. To pass the time, one of them reads novels online. Online novels are currently available through the android market's online novel platform, mainly the Google Play store. The best app has so far been awarded to the app with the most downloads and a star rating on the Google Play store. The Wattpad and Dreame apps have benefits and drawbacks, and there are several comments on the Google Play store site. Application reviews on the Google Play store can be used to determine if an app is good or poor, as well as to look for issues that people have with the app. Descriptive analysis obtained by rating a total of 4137 Wattpad user reviews revealed that 33.12 percent of users strongly dislike, 17.04 percent dislike, 15.71 percent neutral, 11.31 percent like, and 22.82 percent like, while applications Dreame received 10.94 percent users strongly dislike, 13.24 percent dislike, 27.86 percent neutral, 21.85 percent like, and 26.12 percent users strongly like from 3090 reviews. As a result of the rating, Dreame outperforms Wattpad